Stability of Covid-19 Dynamics: A Case Study of Nigeria - Sunday Nwokpoku Aloke; Emmanuel Nwaeze; Louis Omenyi (Britain International for Academic Research (BIAR) Publisher, 2023)
In this paper, a SEIR epidemic model is considered; where individuals in the population are assigned to different compartments of SEIR defined with respect to epidemic status of Covid-19 in Nigeria. The article has demonstrated a simple mathematical model for the transmission of Covid-19 disease taking into account loss of human immunity with the aim that this model proves useful in controlling the possibility of a person contracting Covid-19 twice. When the basic reproduction number means that the Covid-19 free equilibrium solution is locally asymptotically stable. This suggests that the number of new cases of the disease will decrease over time and eventually will vanish as that whcih causes are established. The basic reproduction number and the model analysis (local stability of disease-free equilibrium and disease-endemic equilibrium) of the system were calculated and the stability of the SEIR model was checked.